Концепция счастья: попытка осмысления - Резуненко, К. И. (ХНУРЕ, 2020)
This paper considers the concept of the concept of "happiness", an attempt to comprehend it. The existing models are described in the work, their privileges and disadvantages are considered. A new model is also presented, which describes in more detail some aspects of the concept of "happiness".
Keywords: философия; концепция счастья